Assessment of specific structural and ground-improvement seismic retrofitting techniques for a case study RC building by means of a multi-criteria evaluation. (April 2022) - Requena-Garcia-Cruz, M.V.; Morales-Esteban, A.; Durand-Neyra, P.
Abstract: Existing reinforced concrete (RC) structures might not comply with current seismic codes due to their aseismic design and construction date. By seismically retrofitting them, it is possible to improve their seismic performance to resist the expected seismic loads. However, selecting the best solution is challenging since social and economic issues can affect the choice. Multi-criteria decision making (MCDM) provides an opportunity to overcome the challenge but there are some drawbacks in the available MCDM techniques. This paper reports an improved MCDM-based seismic retrofit: Additional criteria have been included and weighted according to their importance (ductility improvement and damage reduction); Finite element modelling of the case study building has been carried out instead of following methods based on different simplifications; iii) Structural performances have been assessed by determining the damage in local elements instead of following global assessment procedures; Effects of soil-structure interaction (SSI) have been taken into account to ultimately compare different structural and ground-improvement techniques. Consistency and sensitivity analyses have proved the stability of the results and the robustness of the method. It is shown that SSI can increase the seismic damage up to 17%, and regarding the seismic safety verification, the building needs to be retrofitted. Adding fibre reinforcement polymers and steel bracings are the best solutions due to the minimum architectural impact and the outstanding structural improvement, respectively. Nevertheless, the solution preferred is the addition of single steel braces in beam-column joints despite its high maintenance costs. The sensitivity analysis indicates that the most sensitive criteria are the functional compatibility and the reduction of the collapse risk.